1980
DOI: 10.1038/icb.1980.47
|View full text |Cite
|
Sign up to set email alerts
|

GENERATION OF INFLUENZA VIRUS SPECIFIC DELAYED TYPE HYPERSENSITIVITY T CELLS IN VITRO. SECONDARY EFFECTOR CELLS.

Abstract: Summary When spleen cells from mice injected 3 weeks or more previously with influenza A virus (responder cells) are mixed with normal spleen cells exposed 1 h previously lo influenza A virus (stimulator cells) and the mixture cultivated at 37° for 5–6 days, the surviving cell population contains effector T cells (Td) which can mediate delayed type hypersensitivity reactions. If infectious virus is used to prime both the donor mice and to infect the stimulator cells, the cell population also contains cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Since, after intravenous administration, specific blasts maintained in 2 MLC SN localized primarily in the lungs (Engers et al, unpublished observations), it is not surprising that parasite-specific T cells could successfully transfer DTH in normal mice only after local and not after intravenous administration. Similary, it has been observed recently that the local injection of influenza virus-specific T cells generated in vitro was a prerequisite for the successful transfer of a specific DTH reaction (Leung & Ada 1980).…”
Section: Ability Of Lttopica-specific T Blasts To Transfer Delayed Tsupporting
confidence: 67%
“…Since, after intravenous administration, specific blasts maintained in 2 MLC SN localized primarily in the lungs (Engers et al, unpublished observations), it is not surprising that parasite-specific T cells could successfully transfer DTH in normal mice only after local and not after intravenous administration. Similary, it has been observed recently that the local injection of influenza virus-specific T cells generated in vitro was a prerequisite for the successful transfer of a specific DTH reaction (Leung & Ada 1980).…”
Section: Ability Of Lttopica-specific T Blasts To Transfer Delayed Tsupporting
confidence: 67%
“…(Phosphate-buffered saline (PBS) was injected into the left footpad.) Lung or secondary effector cells were injected into the hind footpads 6 h after virus (2x 10' HAU) into the same footpad, or plastic adherent cells were removed from the cell preparations, which could then be injected with virus into the footpad [10]. Footpad swelling was measured 24 h later [8].…”
Section: Methodsmentioning
confidence: 99%
“…However, in these experiments, noninfectious (ultraviolet light (UV)-irradiated) virus was used to elicit the DTH reaction, since it was technically difficult to obtain preparations that contained only infectious virus. The possibility remained, therefore, that infectious virus would sensitize a second population of DTH effector cells to influenza virus, which would be K,D-region-restricted but not detected in our previous assay system because the eliciting antigen was non-infectious [8][9][10][11]. We have recently prepared concentrated preparations of virus which contain infectious virions 0300-9475/80/1200-0481 $02.00 © 1980 Blackwell Scientific Publications 481 and found that injection of mice with infectious virus or restimulation of immune spleen cells in vitro generate two distinct populations of effector T cells which mediate DTH reactions.…”
mentioning
confidence: 95%
“…The same amounts of phosphate-buffered saline, pH 7.2, were injected into the left hind footpads as a control. If infectious virus was used for elicitation of the DTH response, the effector cells were always injected 6 h after injection of virus (2.5 X 10 a HAU) into the same mice footpads (28). Footpad swelling was measured 24 h later as described previously (26).…”
Section: Generation Of Helper T Cells In Vivomentioning
confidence: 99%
“…A recent paper has suggested that there is a requirement for T-T cooperation for the manifestation of a DTH response to the synthetic polypeptide poly(LTyr,LGlu)-poly(DLAla)--poly(LLys) [(T,G)-A--L] (24). Earlier work from this laboratory has studied the DTH response to influenza virus as an antigen, both in vivo (25)(26)(27) and in vitro (28), and on the possible role of the DTH effector cells in the pathogenesis of viral infection (27). We have recently demonstrated that a weak primary DTH response to influenza virus can be obtained in vitro 2.…”
mentioning
confidence: 99%